1990
DOI: 10.1002/pros.2990160405
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of age to histologic grade in prostate cancer

Abstract: We studied 4,968 cases of prostatic carcinoma to determine if there is a relationship between tumor grade and patient age at diagnosis. Cases were stratified into arbitrary age groups and classified as either better differentiated (Grades I and II) or worse differentiated (Grades III and IV). The 4,596 graded cases were distributed by stage as follows: Local 3,451 (75%), Regional 509 (11%), and Distant 636 (14%). When patients in all stages were considered together, the percentage of men with better differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
(13 reference statements)
2
8
0
Order By: Relevance
“…10,11 Several authors studied dedifferentiation by comparing differentiation in metastases and primary tumors 20,21 and concluded that there is a trend toward histological dedifferentiation when prostate carcinoma metastasizes to regional lymph nodes. It could be argued however, that these observations are the consequence of a higher potential for metastasis of poorly differentiated tumor cells, rather than dedifferentiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 Several authors studied dedifferentiation by comparing differentiation in metastases and primary tumors 20,21 and concluded that there is a trend toward histological dedifferentiation when prostate carcinoma metastasizes to regional lymph nodes. It could be argued however, that these observations are the consequence of a higher potential for metastasis of poorly differentiated tumor cells, rather than dedifferentiation.…”
Section: Discussionmentioning
confidence: 99%
“…We investigated whether our data show a relation between Gleason score, clinical T-stage (cT-stage) and age at diagnosis as noted by others. 10,11 We used the findings to discriminate between 2 MISCAN simulation models that do not allow (Model I) or do allow (Model II) dedifferentiation in the screendetectable phase. A significantly better fit to observed data of Model II is a strong indication of dedifferentiation that could be prevented by early detection and treatment.…”
mentioning
confidence: 99%
“…First, we examined the data for conformity with previously described race, stage, age, and grade differentials of prostate cancer [17][18][19]. Specifically, for race (black vs. white), stage (localized, regional, distant), age tertiles (< 65 years, 65-74 years, and Ն 75 years), and grade (well, moderate, poorly, and undifferentiated) we analyzed the following relationships: 1) race-stage, 2) race-age at diagnosis, 3) stagegrade, and 4) age at diagnosis-grade.…”
Section: Discussionmentioning
confidence: 99%
“…A second explanation is that tumour biology may change with age, such that older patients present with more advanced or aggressive tumours [11]. Although age/stage relationships have been described for several other malignancies [7,24,25], the strongest relationships have been reported for tumours that are amenable to screening (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Four previous studies have examined changes in prostate cancer stage with increasing age [6][7][8][9]; whereas two found a change toward more early-and distant-stage disease in the oldest group ( ≥ 75 years) [7,9], two others found no age/stage relationship [6,8]. Two studies have examined the age/grade relationship in a broadly sampled group of men with prostate cancer [10,11]; one reported an increase in grade with increasing age [11], whereas the other found no such relationship [10].…”
Section: Introductionmentioning
confidence: 99%